VEREDAS: CHARACTERIZATION, DISTRIBUTION AND IMPORTANCE (Editora Impacto Científico, 2025)
Veredas are unique formations found only in Brazil. They are a typical vegetation formation of the Cerrado. Although still little known, they contain endemic fauna and flora species. They are characterized not only by the outcrop of the aquifer, but also by soil type, phytophysiognomy, and species present. Since the first Brazilian Forest Code, veredas have been permanent preservation areas. The Forest Code establishes that veredas are considered permanent preservation areas, with a marginal strip of 50 meters from the permanently marshy or wetland area. Despite their relevance and importance, they still present problems related to conservation, demarcation, and disorderly land use and occupation.DOI: https://doi.org/10.56238/edimpacto2025.090-088